2008
DOI: 10.1007/s11240-008-9374-0
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and xanthone content of Gentianella austriaca shoot cultures

Abstract: Shoot cultures of Gentianella austriaca (A. & J. Kerner) Dostal established from seedling epicotyls were maintained on MS medium supplemented with 2.22 lM BA and 0.54 lM NAA. A characteristic feature of these cultures was precocious flowering, which appeared in all rapidly elongating shoots. Flower development arrested shoot elongation and multiplication of shoot cultures. Continuous shoot propagation was possible only by use of small axillary or adventitious buds as explants for subculturing. Flowering could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…2,4-D and NAA are essential for inducing callus and shoots in Leymus chinensis (Sun and Hong 2010). BA increases the production of xanthones in Gentianella austrica shoot cultures (Vinterhalter et al 2008). Interestingly, the types of auxin and cytokinin and the ratio between the two are also important not only for increasing the percentage of callus production but also for callus growth (Zenk 1978).…”
mentioning
confidence: 99%
“…2,4-D and NAA are essential for inducing callus and shoots in Leymus chinensis (Sun and Hong 2010). BA increases the production of xanthones in Gentianella austrica shoot cultures (Vinterhalter et al 2008). Interestingly, the types of auxin and cytokinin and the ratio between the two are also important not only for increasing the percentage of callus production but also for callus growth (Zenk 1978).…”
mentioning
confidence: 99%
“…We compared the efficiency of MS and WPM media for the induction of organogenesis and tested several combinations of phytohormones. Induction of organogenesis was also successfully used for the propagation of many Gentiana species such as G. pneumonanthe (Lamproye et al 1987), G. kurroo (Sharma et al 1993), G. acaulis, G. cruciata, G. lutea, G. purpurea, (Momčilović et al 1997;Hayta et al 2011), G. cerina, G. corymbifera (Morgan et al 1997), G. punctata (Butiuc-Keul et al 2005), G. austriaca (Vinterhalter et al 2008) and G. dinarica (Vinterhalter et al 2012;Krstič-Miloševič et al 2013). Optimizing micropropagation is not straightforward since it is a complex process involving a sequence of developmental stages that are influenced by numerous endogenous and exogenous stimuli, which include especially phytohormones, such as auxins and cytokinins.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained for Gentianella austriaca shoot cultures. By high-performance liquid chromatography, it was shown that the shoot cultures contained nearly two times less xanthones than plants growing in nature (Vinterhalter et al 2008).…”
Section: Total Xanthone Content In Cultured Tissuesmentioning
confidence: 99%